Biomolecular condensates in cancer cell biology: interleukin-6-induced cytoplasmic and nuclear STAT3/PY-STAT3 condensates in hepatoma cells - Sehgal, Pravin B. (Contemporary Oncology/Współczesna Onkologia, 2019)
We highlight previous incompletely understood cell biology data in the STAT3 signaling field with respect to interleukin-6 (IL-6)-induced activation of this transcription factor in hepatoma cells to generate cytoplasmic and nuclear STAT3 bodies. We provide a novel re-interpretation of the previous observations. We show that IL-6-induced GFP-STAT3/PY-STAT3 cytoplas-mic and nuclear bodies represent phase-separated biomolecular condensates. These structures represent examples of a cytokine-induced phase transition which occurs within 10–15 min of exposure to the cytokine, and which was Tyr phosphorylation dependent. Evidence that these IL-6-induced cytoplasmic and nuclear GFP-STAT3 bodies in live cells represented phase-separated condensates came from the observation that 1,6-hexanediol caused their disassembly within 30–60 seconds. Moreover, these STAT3 condensates also showed rapid tonicity-driven phase transitions – disassembly under hypotonic conditions and reassembly when cells were returned to isotonic medium. That STAT3 condensates were rapidly disassembled in hypotonic buffer commonly used for cell fractionation points to a limitation of studies of STAT3 biochemistry using hypotonic swelling and mechanical breakage. Overall, the new data help reinterpret IL-6-induced cytoplasmic and nuclear STAT3 bodies as phase-separated biomolecular condensates, and bring the concept of membrane-less organelles to the cytokine-induced STAT transcription factor field and cancer cell biology.